Improvement of BER using Pilot Insertion with SSS Algorithm in Sparse Channel Estimation - R, Suganya; D, Kumutha; N, Amutha Prabha (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
This paper deals with the pilot placement problem for sparse channel estimation in OFDM systems. However, the selection of pilot tones significantly affects channel estimation performance. The need of optimal pilot placement for sparse channel estimation, in the sense of minimum mean-square error through an exhaustive search of all possible pilot placements is extremely computationally intensive. Reduction in computational complexity and simultaneously maximizing the accuracy of sparse channel estimation, the cross-entropy optimization is proposed to determine the optimal pilot placement by using Stochastic Search Scheme (SSS) algorithm. The simulated results can be obtained for cross entropy optimization method with stochastic search algorithm in channel estimation in OFDM systems.